Analysis of Total Plate Count (TPC) in Pukis Cakes Sold in Traditional Markets - Makhabbah Jamilatun; Eka Nanda Safitri (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Pukis cake is a traditional Indonesian cake. Pukis cakes are much liked by the public because pukis cakes have a savory and sweet taste so they become one of the attractions of the cake. Pukis cake has a lot of nutritional content. One of the parameters used in determining the feasibility and safety of food is to measure the microbiological content in food. Biological hazards, especially microbes in food, need attention because this type of hazard is often the causative agent of food poisoning cases. This research was conducted to know the Total Plate Count (TPC) in Pukis Cake. The study began with the isolation of microorganisms from Pukis Cake samples, followed by the calculation of the Total Plate Count (TPC). The results showed that the Total Plate Count (TPC) of the sample 1 was 1.19x104 colonies/g (>1x104), the sample 2 was 19.44x104 colonies/g (>1x104), samples 3 were 11.35x104 colonies/g (>1x104), samples 4 were 19.93x104 colonies/g (>1x104). These results show that the pukis Total Plate Count (TPC) exceeds the standard set by SNI Number 7388 of 2009, namely TPC with a maximum limit of 1×104 colonies/g.